ANALISIS AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN FISIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN STEM (Pokok Bahasan Gaya dan Hukum Newton) - Ainul Kiromah; Sudarti Sudarti; Rohatin Rohatin (JURNAL PEMBELAJARAN FISIKA, 2020)
PBL (Problem Based Learning) learning model with STEM approach can improve student learning activities. Learning activities undertaken are one indicator of students' desire to learn. Student learning activities that occur in the learning process in the form of drawing activities, oral activities, listening activities, and mental activities. The purpose of this study was to determine the effect of Problem Based Learning learning models with the STEM approach to student learning activities. This type of research used was pra-experimental with desain One Shot Case Study. and the sample of this study was students of class X IL2 SMKN 2 Jember.